Pengembangan Media Pembelajaran Mandiri Berbasis Smartphone Pada Materi Kubus Tingkat MTs - Nadiya Yusuf; I Nyoman Arcana (Universitas Sarjanawiyata Tamansiswa, 2018)
The present study aimed to (1) develop media-based learning of smartphone for learning mathematics in junior school, (2) to know the feasibility of media-based smartphone made. This research is a research and development (Research & Development), which is a research used to develop or validate the products used in learning. The development method used in this study follows a simple development procedure suggested by Borg & Gall consisting of five steps, namely (1) product analysis to be developed, (2) initial product development, (3) expert validation and product revision, 4) limited trial and product revision, (5) main trial and final product. The result of this study is media learning with the title